Faktor Risiko Terjadinya Manifestasi TB Paru Pada Penderita DM Tipe 2 Dengan Tes Mantoux Positif - Etik Lusiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: DM disease has a high risk to progress from latent TB to be active TB because of immune cell function defect. A few researches proved the use of prophylaxis therapy for latent TB infection for the patients with positive mantoux test. In Indonesia INH prophylaxis treatment with control management of the risk factor to the occurance of lung TB for type 2 DM patients with positive mantoux test needed to be paid attention to prevent getting TB. A long term prophylaxis treatment needed to be considered because of hepatotoxicity risk.Method: The research was case control study, the research was done from May to July 2017 at RSUD Dr. Soetomo and one of private hospitals in Surabaya. The number of sample was 60 respondents who consisted of case and control groups using consecutive sampling technique. The data collection used interviews and mantoux test practice. The statistics test used chi-square test.Result: Type 2 DM patients with positive mantoux test without manisfestation of TB lung 10 (33,3%) male and 20 (66,7%) female. Chi square test result shared that there was a correlation between BMI and DM control practice for type 2 DM patients with the occurrence of lung TB. Logistic regression test result showed that education (p=0,023 OR=5,897), BMI (p=0,004 OR=10,197) and DM control practice (p=0,003 OR=7,997) for type 2 DM patients who has the risk of lung TB occurance.Conclusion: The dominant factor of education, BMI and DM control practice that was influential to the occurance of lung TB was BMI.